2010
DOI: 10.1016/j.tins.2009.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Senescent synapses and hippocampal circuit dynamics

Abstract: Excitatory synaptic transmission is altered during aging in hippocampal granule cells, and in CA3 and CA1 pyramidal cells. These functional changes contribute to age-associated impairments in experimentally-induced plasticity in each of these primary hippocampal subregions. In CA1, plasticity that is evoked by stimulation shares common mechanisms with the synaptic modification observed following natural behavior. Aging results in deficits in both artificially- and behaviorally-induced plasticity, which may in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
152
2
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 174 publications
(162 citation statements)
references
References 92 publications
5
152
2
3
Order By: Relevance
“…These results complement the effects on synaptic function, because synaptic processes are also calcium-dependent. We and others have shown that calcium dyshomeostasis plays a key role in brain-aging processes (44,56,71) and have demonstrated that vitamin D reverses calcium-related electrophysiological markers of brain aging (24,27). Together, these results suggest that the effects of vitamin D on calcium regulation and synaptic function may interact to counter cognitive decline with aging.…”
Section: Additional Pathways Potentially Related To Cognitive Functionmentioning
confidence: 61%
See 2 more Smart Citations
“…These results complement the effects on synaptic function, because synaptic processes are also calcium-dependent. We and others have shown that calcium dyshomeostasis plays a key role in brain-aging processes (44,56,71) and have demonstrated that vitamin D reverses calcium-related electrophysiological markers of brain aging (24,27). Together, these results suggest that the effects of vitamin D on calcium regulation and synaptic function may interact to counter cognitive decline with aging.…”
Section: Additional Pathways Potentially Related To Cognitive Functionmentioning
confidence: 61%
“…Compared with the low-and medium-VitD3 groups, the highVitD3 group had a significantly steeper I/O slope. These results suggest that high VitD3 may improve neuronal excitability, which is known to decrease with age (44). However, this increased (Table 1) to an approximate twofold increase in 25OHD.…”
Section: Significancementioning
confidence: 81%
See 1 more Smart Citation
“…There is significant evidence suggesting that synaptic impairment, rather than neuronal loss, may be the leading cause of cognitive deterioration (1)(2)(3). However, the mechanisms that underlie this synaptic impairment remain poorly understood.…”
mentioning
confidence: 99%
“…It is widely believed that learning deficits within the aging brain result from reduced synaptic density and plasticity (3). Most studies so far have focused on dendritic spines, the postsynaptic sites of excitatory synapses.…”
mentioning
confidence: 99%